Interdisciplinarity in Technology Enhanced Learning: An Interview Study. Issue 1 (10th August 2018) - Scanlon, Eileen; Conole, Gráinne
This paper explores the influence of the concept of interdisciplinarity on the work of educational technologists and others involved in technology-enhanced learning (TEL) research. There is a growing recognition of the need for interdisciplinarity in solving complex research problems in many areas of science. Technology-enhanced learning is a relatively young area of research adopting a multidisciplinary approach to investigating the use of technologies for learning. This makes it a field that is worthy of exploration in terms of how the ways of working developed by its practitioners inform our understanding of the challenges of the field as well as its benefits. This paper reporting on work commissioned by the Joint Research Councils' programme on Technology Enhanced Learning provides a discussion of the growing literature on this topic, and a study of the working practices of academics in TEL research. An interview study of 18 participants was conducted as part of the project. The paper reports on the key findings from the interviews and concludes with some practical suggestions to help participants deal with the challenges posed by interdisciplinary working in TEL research.